Optimization Analysis of Track Following for Double-articulatedVehicle with Full-axle Steering - ZHOU Sheng; ZHANG Chenlin; ZHOU Chengming; ZHONG Hanwen (Kongzhi Yu Xinxi Jishu)
In order to optimize passability and reduce lane occupation of double-articulated vehicles, based on the three-unit autonomous-rail rapid tram developed by CRRC Zhuzhou Institute Co., Ltd., it analyzed road occupancy width and track following error of double-articulated vehicles with full-axle steering during turning. According to the kinematic model of single unit, trajectory deviation function and its optimization analysis were obtained during the double-articulated vehicle steering. Kinematic simulation and path deviation calculation of the double-articulated vehicle with first-order delay steering were completed at the last part. Simulation results show that the road occupancy width of the vehicles with first order delay steering is only 23% of that of vehicles with non-full axle steering. So, the first-order delay steering method established by means of the above method can effectively improve the following accuracy of vehicles, reduce the road occupancy width of vehicles, and improve the applicability and economy of double-articulated vehicles.